VIRULENCE GENOTYPE AND PHYLOGENETIC GROUPS IN RELATION TO CHINESE HERB RESISTANCE AMONG ESCHERICHIA COLI FROM PATIENTS WITH ACUTE PYELONEPHRITIS - YanQing, Tong; ShuQing, Sun; Ying, Chi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Clinical isolates of herb-resistant uropathogenic E. coli were isolated. It was possible that the virulence genotypes and phylogenetic background of E. coli differed between Chinese herb-resistant E. coli and -susceptible isolates. For this purpose, the prevalence of virulence factors (VFs) and phylogenetic background, with regard to Chinese herb resistance, among E. coli strains causing acute pyelonephritis from China were investigated. Materials and Methods: E. coli isolates from patients with acute pyelonephritis were used in this study. Standard disc diffusion methodology was used to test the susceptibility of Chinese herbal concoction against E. coli strains. Multiplex PCR amplifications employed three markers (chuA, yjaA, and TSPE4.C2) to classify E. coli isolates into one of four phylogenetic groups (group A, B1, B2, or D). The isolates were also tested for 14 virulence-associated traits (VFs) of uropathogenic E. coli.Results: A total of 115 E. coli strains were isolated. 79 (68.7%) were susceptible and 36 (31.3%) were resistant to the herbal concoction. 20.9% of the isolates encoded three or more of VFs for which they were screened, with 13.9% in susceptible isolates and 36.1% in resistant isolates. The key VFs (fyuA and/or iutA siderophores) present in >80% of isolates. The papA and papC adhesins were detected in the majority of resistant isolates (72.2% and 63.9% respectively). 78.5% of susceptible isolates belong to phylogenetic groups A, while 83.3% of resistant isolates belong to group B2. Conclusion: PapA and papC are significant VFs with an essential role in contributing to Chinese herb-resistance. Chinese herb-resistance is associated with a shift towards more virulent strains and B2 phylogenetic group.